MICROZONATION OF GREATER BANDUNG AREA FOR POTENTIAL EARTHQUAKE HAZARD ANALYSIS - Mamonto, Faisal
Greater Bandung area, West Java, is a basin zone composed of relatively soft sedimentary rock profiles located in an active tectonic zone. This condition makes the Greater Bandung area have the potential for amplification of ground shaking due to vibrations caused by earthquake events. In this study, the Horizontal to Vertical Spectral Ratio (HVSR) microtremor method is used for microzonation studies that aim to determine physical parameters such as dominant frequency, dominant period, amplification, earthquake vulnerability index, sediment thickness, shear wave velocity model at a depth of 30 meters, peak ground acceleration and ground shear Strain. These parameters can be used as object for a comprehensive analysis of potential hazards in the Greater Bandung area. The data used in this study is temporary seismic station observation data in Greater Bandung which is a research collaboration between ITB and Australian National University in 2014. The number of seismic observation points is 51 points covering the research area. The duration of data recording is 6 months. For the further analysis, we used observational data for 2 hours at night with a time range from 20.00 to 23.00 local time. The waveform data at each observation point is processed using Geopsy software to obtain the HVSR curve. The resulting HVSR curve gives the values of the dominant frequency and maximum amplification factor. Dominant frequency values and maximum amplification factors become the basis for obtaining dominant period values, earthquake vulnerability index, peak ground acceleration (PGA) and ground shear Strain (GSS). Based on the HVSR curve obtained, it can be used as input for the calculation of the estimated 1-D shear wave velocity (Vs) profile. The results of the Vs value and the parameters related to the dynamic response of the soil become the basis for the analysis of zones that are susceptible to earthquake shocks. The results of an integrated analysis related to the potential for earthquake hazards show that the southeastern area of the study which includes Bandung Regency has a relatively high risk. With Kg values 50 - 154, GSS 1 ???? 10?3 - 13,3 ???? 10?3, PGA 104 - 130 gal and Vs30 25 - 81 m/s